Programing AAC just-in-time for beginning communicators: the process. (2nd October 2019) - Holyfield, Christine; Caron, Jessica; Light, Janice
Abstract: Individuals who have limited or no speech as a result of intellectual and developmental disabilities and who are beginning communicators (i.e., are learning early linguistic skills such as first words and early semantic relations) require augmentative and alternative communication (AAC) to build both their expressive communication and their internal language structures. Programing AAC just-in-time is a promising clinical approach to intervention for beginning communicators because of its alignment with early language development theory. Early research efforts also provide emerging evidence to support its theoretical benefits. This paper describes a six-step process for programing AAC content just-in-time for beginning communicators. It highlights clinical challenges and considerations for each step, provides case examples of using the process with beginning communicators, and highlights potential limitations and future research directions related to the just-in-time programing of AAC for beginning communicators.